The advertisement call of Scinax funereus (Cope, 1874) (Anura: Hylidae) from Ecuadorian Amazon - Read, Morley; Lopes, André Gomes (Zootaxa, 2020)
Scinax Wagler currently harbors 72 treefrog species distributed throughout the Neotropical region, occurring from Mexico to Argentina and Uruguay, and also in some Caribbean islands (Frost et al. 2020). The genus has a high level of cryptic diversity, with its actual number of species currently considered to be underestimated (Fouquet et al. 2007, Ferrão et al. 2016). Scinax funereus (Cope) is a medium-sized species described from Moyobamba, San Martín Department, northern Peru, with occurrences reported from the Peruvian and Ecuadorian Amazon (Duellman & Wiens 1993), southern Colombia (Lynch 2005), and from the Brazilian states of Acre (Bernarde et al. 2011) and Amazonas (Ramalho et al. 2016). Duellman (1978) reported that the advertisement call of S. funereus “consists of a moderately long, rather high-pitched, single note”, but as no call recording was obtained at the time, it was not described. Although Read (2000) published the species’ call in the audio form in a compact disc (CD), it was not formally described. Given this, herein we provide the first formal description of the advertisement call of S. funereus.